Inventory of Electronic Waste (E-Waste) and Residues in Junkshops: A Step Towards Residual Waste Management - Ventabal, Rachel Alexis S.; Cruz, Zia May S.; Santos, Jasper F.; Basilio, Eleonor R. (International Journal of Environment, Engineering and Education, 2024)
The improper management of Waste Electrical and Electronic Equipment (WEEE) constitutes a critical global environmental challenge, with a significant proportion of e-waste ending up in landfills, posing substantial ecological and health risks. In the Philippines, particularly in areas like Marilao, many individuals rely on the recycling of e-waste for their livelihoods, primarily through junkshops and informal recycling networks. Despite providing economic benefits, these practices often result in substantial residual waste, exacerbating landfill overflow and environmental degradation. This study aims to establish a detailed e-waste inventory and propose practical strategies for improving residual waste management. This research used a mixed-method approach to collect data via surveys, interviews, and direct observations at selected junkshops in Marilao. The findings enabled a comprehensive categorization of e-waste based on economic value, highlighting "temperature exchange equipment" as the most economically valuable category while identifying "small IT and telecommunication equipment" as the least. Among the significant residual wastes identified were base/black plastics, styrofoam, and glass, which are commonly mishandled. The study proposes several management strategies, including partnerships with local governmental bodies and recycling companies to enhance recycling processes, improving dismantling techniques to reduce waste, and implementing rigorous waste segregation practices to prevent contamination and improve recycling rates. This expansion is critical for a more comprehensive understanding and monitoring of e-waste management practices, facilitating the development of more effective and sustainable waste management solutions. By adopting these strategies, junkshops and informal recyclers can optimize e-waste management, reducing environmental impact while maintaining economic viability.